Post a New Question

math

posted by .

Q: Convert 4x^2 + 4y^2 -8x -16y -29 = 0 into standard form.

I first started by pairing the like terms together, getting:
4x^2 -8x + 4y^2 -16y = 29

The next step, I'm a little confused. I know I need to complete the square, but I'm not sure how to fully factor out the above equation before doing so. Can someone help me getting the factored form of the above equation?

Thanks!

  • math -

    4x^2 -8x + 4y^2 -16y = 29
    4(x^2 - 2x + ...) + 4(y^2 - 4y + ... ) = 29
    4(x^2 - 2x + 1) + 4(y^2 - 4y + 4) = 29 + 4 + 16
    4(x-1)^2 + 4(y-2)^2 = 49
    divide by 4
    (x-1)^2 + (y-2)^2 = 49/4

    looks like a circle with centre at (1,2) and radius 7/2

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

More Related Questions

Post a New Question